Studying the authenticity of the golden element from a mongolian warrior's armor by physicalchemical methods - Indutnyi, Volodymyr; Merezhko, Nina; Pirkovich, Kateryna (Eastern-European Journal of Enterprise Technologies, 2019)
We report results from an expert study into the historical artifact of the XIV–XV centuries ‒ the golden armor element of a Mongol warrior. The obtained results allowed us to establish signs of authenticity in the historical values made of gold in a given chronological period. The microstructure of the object was investigated at a magnification of 10–20 times, revealing significant fragility and frailty of the metal. At magnification by 150–200 times, we found the system of cracks with triple points, individual caverns, and a cavernous character of the fracture. Furthermore, we have revealed many dislocations of fractures and traces of the metal flow at the surface of the item, as well as traces of tools that had been used to clean it. At magnification by 2,000 times, we found an extremely complex morphology of the metal with numerous caverns, as well as the surface of partially dissolved metal, which retains the contours of ancient scratches. We have established that the deeper parts of the alloy partially retained their chemical composition, and the concentration of gold in them is only 62–80 %, while the alloy was refined at the surface in a natural way, therefore, the gold content in it was determined to be within 81–98 %. In addition, in the deeper parts of the alloy, silver concentrations are larger compared with the surface layers, because silver compounds are chemically more active and are carried away from the surface under the action of external factors. We have determined a list of features that indicate the authenticity of the object, and which are unambiguously detected using an electron microscope, as well as based on the results of studying the chemical composition of the surface of the artifact by emission method. In our opinion, it is efficient to use electron microscopy in experts' work in order to confirm authenticity, to identify signs of forgery and traces of restoration of artifacts made from gold alloys